Status of the Pythiaceae (Straminipila) in Argentina - Palmucci, Hemilse E. (2011)
The genus Pythium (Pythiaceae (Peronosporomycetes - ex Oomycetes), Kingdom Straminipila) includes important pathogens, affecting a wide range of hosts of economic value, causing damping-off and decline of herbaceous and wooded plants due to rootlets rot. In order to acquire a more comprehensive vision of Pythium in Argentina, a review and an updated report of recent progress in this matter was carried out since the first reports in the late XIX century till October 2009. Information was taken from printed and on line primary and secondary sources such as Proceedings of national and international Scientific Meetings, Bulletins from National Institutions and Universities, periodical Journals, books and data bases. The information was analyzed and categorized, thus updating the number of species of this genus, their geographical distribution, hosts affected, and symptoms. So far 18 species have been cited affecting, 247 hosts. The greatest number of hosts is affected by P. ultimum and P. debaryanum, followed by P. irregulare and P. aphanidermatum. The diversity of Pythium species in the world suggests that perhaps a wider variety of species, still not cited, could be present in Argentina. Projects dedicated to surveying the presence and identification of Pythium spp are necessary.